Independence of face identity and expression processing: exploring the role of motion - Lander, Karen; Butcher, Natalie (Frontiers in Psychology, 2015)
According to the classic Bruce and Young (1986) model of face recognition, identity and emotional expression information from the face are processed in parallel and independently. Since this functional model was published, a growing body of research has challenged this viewpoint and instead support an interdependence view. In addition, neural models of face processing (Haxby, Hoffman & Gobbini, 2000) emphasise differences in terms of the processing of changeable and invariant aspects of faces. This article provides a critical appraisal of this literature and discusses the role of motion in both expression and identity recognition and the intertwined nature of identity, expression and motion processing. We conclude, by discussing recent advancements in this area and research questions that still need to be addressed.